OVERCOMING UNDERDEVELOPMENT, ERADICATING POVERTY AND INTERNATIONAL ACTION OF MUNICIPALITIES: THE EXAMPLE OF THE CITY OF SAO PAULO - Simini, Danilo Garnica; Laisner, Regina Claudia [UNESP] (Univ Estado Rio Janeiro, 2018)
The Federal Constitution presents objectives for the State, in terms of the development and consolidation of citizenship, understood as multidimensional phenomena, which require compatible public policies. Recently Brazilian municipalities have developed public policies in this direction, through international action, being the city of Sao Paulo pioneer in this practice. The article aims to analyze, specifically, the public policies of the Municipal Secretariat of International Relations of Sao Paulo that sought to contribute to the development and eradication of poverty, starting from the hypothesis that the international municipal action constitutes an adequate alternative for these purposes. Initially, the potentialities of constitutional dirigisme in terms of public policy orientation are discussed; then the challenges of development and the fight against poverty, and their policies and, soon after, the role of the international action of municipalities as the generator of municipal public policies, particularly the example of Sao Paulo. Finally, the selected projects are analyzed, in order to observe to what extent the presented hypothesis is sustained. It was concluded that the projects indicate that the international performance of Sao Paulo is compatible with the constitutional precepts, since they have been multifaceted, dealing with themes such as health, education, culture and employment, fundamental for overcoming underdevelopment and eradicating poverty.
Keywords: Public Policies; Development; Poverty; International Action of Municipalities; Municipal Secretary of International Relations and Federative Sao Paulo